Characterization and traceability of two generations of standard reference material for the measurement of vitamin K1(phylloquinone) at endogenous concentrations in human plasma and serum. (19th April 2022) - Card, David; Freke, Ella; Harrington, Dominic
Abstract: Vitamin K is an essential micronutrient required for blood coagulation, regulation of vascular calcification and bone mineralization. Plasma and serum measurements of vitamin K1 (phylloquinone, K1 ) made using high‐performance liquid chromatography with fluorescence detection, or tandem mass spectrometry are used clinically and in population studies to assess vitamin K status. Standard reference materials provide a validation tool for laboratories, helping assure clinical diagnosis and the comparability of data from different populations. We manufactured two K1 standard reference materials, in 2009 (KEQAS SRM‐001) and in 2019 (KEQAS SRM‐002). The target concentrations of K1 were assigned to each SRM using the All Laboratory Trimmed Mean of results reported by selected laboratories enrolled in the Vitamin K External Quality Assurance Scheme (KEQAS). The assigned concentrations of K1 for KEQAS SRM‐001 and SRM‐002 were 0.25 and 0.36 μg/L respectively. In 2019 KEQAS SRM‐001 was re‐analysed simultaneously with KEQAS SRM‐002 to provide traceability between the two standards, therefore aiding comparability of analysis performed using these materials. Both standards were stored as aliquots at −80°C in the dark; annual re‐analysis of the materials indicated that K1 is stable for at least 12 years in these conditions.